2019
DOI: 10.18805/ijare.a-4737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biodegradable urban waste compost on growth and yield of maize (Zea mays L.)

Abstract: A field experiment was conducted at Zonal Agricultural Research Station, V. C. Farm, Mandya, to study the effect of biodegradable urban waste compost on growth and yield of maize during kharif season of 2014 and 2015. The pooled data of two years indicated that, the grain yield of maize was significantly higher in recommended dose of fertilizer (150:75:40 kg NPK/ha) + Farm yard manure (FYM) @10 t/ha (6995 kg/ha) as compared to no fertilizer application. However, it was on par with application of 50% N as ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…These herbicides controlled the weeds up to 35-40 days after application and later intercultivation controlled the weeds. The results were in line with the findings of Manalil et al [13], Miller et al [14], Yogananda et al [15], Iqbal et al [11], Tariq et al [12] and Chen et al [4].…”
Section: Total Weed Dry Matter (G M -2 )supporting
confidence: 90%
“…These herbicides controlled the weeds up to 35-40 days after application and later intercultivation controlled the weeds. The results were in line with the findings of Manalil et al [13], Miller et al [14], Yogananda et al [15], Iqbal et al [11], Tariq et al [12] and Chen et al [4].…”
Section: Total Weed Dry Matter (G M -2 )supporting
confidence: 90%
“…These findings were support the research of Moe et al (2019) in which, the combined application of organic and inorganic fertilizers enhanced growth and yield attributes of rice. Yogananda et al (2019) also reported that the complementary application of inorganic fertilizer and urban waste compost produced significantly higher maize yield. Like grain yield, the highest straw yield of (7.71 t ha -1 ) was obtained under T 2 (MSWC @ 5 t ha -1 + 75 % RDF) condition with 49.41% increase over control.…”
Section: Effects Of Mswc Application On the Yield Of Rice (Cv Brri Dh...mentioning
confidence: 95%
“…As a costly input, the use of long-term application of unbalanced chemical fertilizer is one of the causes of lower rice production (Moe et al, 2019) comprising negative impact on soil properties (both physical and chemical) and crop productivity which ultimately causes soil deterioration, pollution, etc. (Yogananda et al, 2019;Aktar et al, 2018). Application of organic amendments with chemical fertilizers significantly reduce fertilizer cost, environmental degradation and replenish soil fertility to obtain agricultural sustainability (Sultana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%